The architecture of faith: Clerics, Indians and struggles in the doctrines of the Tarapacá desert, 16th-19th centuries - Díaz Araya, Alberto (2013)
In this article we analyse two important aspects of evangelism among indigenous populations in northern Chile from institutions called “parish of Indians” and “brotherhood”. In this way, based on an extensive review of documents deposited in domestic and foreign archives, we reconstruct Tarapaca’s ecclesiastical scene since the early Colony to Republic, and elucidate the most significant problems that affected Andean indigenous parishioners and that were directly related to the actions of church ministers present in Tarapacá, which would have had a great impact on local Andean religious practices.